Girls’ physical activity levels during organized sports in Australia - Guagliano, Justin M.; Rosenkranz, Richard R.; Kolt, Gregory S. (My University, 2013)
Purpose: The primary aim of this study was to objectively examine physical activity (PA) levels of girls during organized sport (OS), and to compare the levels between games and practices for the same participants. Secondary aims of this study were to document lesson context and coach behavior during practices and games. Methods: Participants were 94 girls recruited from 10 teams in three OS (netball, basketball, soccer) from the Western Suburbs of Sydney. Each participant wore an ActiGraph GT3X monitor for the duration of one practice and one game. The SOFIT was concurrently used to document lesson context and coach behavior. Results: Girls spent a significantly higher percentage of time in moderate-to-vigorous PA (MVPA) during practices compared to games (33.8% vs. 30.6%; t = 2.94, P < 0.05). Girls spent about 20 min/hr in MVPA during practices and about 18 min/hr in MVPA during games. An average of 2,957 and 2,702 steps/hr were accumulated during practice and games, respectively. However, girls spent roughly two-thirds of their OS time in light PA or sedentary. Based on SOFIT findings, coaches spent a large proportion of practice time in management (15.0%) and knowledge delivery (18.5%). An average of 13.0 and 15.8 occurrences/hr were observed during games and practices where coaches promoted PA. Conclusion: For every hour of game play or practice time, girls accumulated approximately one-third of the recommended 60 minutes of MVPA time and about one-quarter of the 12,000 steps that girls are recommended to accumulate daily. For this population, OS appears to make a substantial contribution to recommended amounts of MVPA and steps for participating girls. OS alone, however, does not provide amounts of PA sufficient to meet daily recommendations for adolescent girls.
Keywords: Physical activity; Children; Adolescents; Youth sports; MVPA; Accelerometer; SOFIT